(untitled) (Eurasian Journal of Philology Science and Education, 2022)
There are cases of committing offenses in the course of the activity, use of the language in various spheres of society’s life. Problems in this regard are considered at the intersection of linguistics and law, and require theoretical and methodological research. In view of this, the article considers issues that arise in the course of linguistic expertise of the controversial text in a lawsuit for damage to the honor, dignity and business reputation of a person and ways to resolve them. The subjective assessment of the data statement and the possibility of expressing the objective data and the role of semantic analysis in their differentiation are presented to the attention of experts. Consequently, the role of grammatical markers of subjective modality and the possibilities of semantic analysis in determining information that can be verified for compliance with reality are analyzed. In the semantics of explicit and implicit language units, the nature of the content of information that can be checked for compliance with reality is indicated as one of the main features of the data statement. The possibility of identifying data that can be inspected for compliance with reality by mutually distinguishing data (fact) and factoids of a factual nature is analyzed on the basis of specific examples. It also indicates the significance in the forensic linguistic expertise of the scientific provisions of the proposition theory in the part in which the subject of the truth of a sentence, utterance, speech acts is determined. The article is devoted to specialists in the field of forensic linguistic expertise. Key words. Linguistic expertise of negative information, assertion of fact, propositions in a sentence, explicit and implicit language units, semantic analysis, the role of grammatical markers.